The role of the pharmacy navigator in hematopoietic stem cell transplantation - Lago, Giovanna Fernandes; Santos, Carolina Ferreira dos; Diniz, Andressa Pinheiro; Otuyama, Leonardo Jun; Sforsin, Andrea Cassia Pereira; Pinto, Vanusa Barbosa (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Hematopoietic stem cell transplantation (HSCT) is a complex procedure that requires rigorous pharmacotherapeutic management. This study aimed to describe the role of the pharmacy navigator in HSCT at the Hospital das Cl.nicas of the Medical School of the Universidade de S.o Paulo. For the assessment of pharmacist activities in HSCT, a literature review was conducted, alongside direct observation of pharmaceutical activities in different HSCT phases at the service: pre-transplant, hospitalization, discharge, and outpatient follow-up. It was observed that the pharmacy navigator plays a crucial role, including medication reconciliation, dose adjustments, monitoring drug interactions and toxicities, and providing health education to patients and the multidisciplinary team. Pharmacotherapeutic follow-up contributed to reducing medication errors, improving treatment adherence, and ensuring safer administration of immunosuppressants and antimicrobials. In conclusion, the presence of a pharmacy navigator in HSCT is essential to optimize treatment, prevent complications, and enhance patients’ quality of life, consolidating this professional as a key member of the multidisciplinary healthcare team.